LOCAL COMMUNITY PARTICIPATION IN THE VILLAGE WEBSITE DEVELOPMENT IN GIANYAR BALI - Tanjung, Sumekar (PEOPLE: International Journal of Social Sciences, 2017)
This study aims to describe the forms of local community’s participation in the village website development. Village plays the strategic role in the national development plan. The program that supports this development plan is the Integrated Broadband Village Program by the Ministry of Communications and Informatics through the provision of the desa.id. In 2016, domain users increased by 84% compared to 2015. The Ministry of Communications and Informatics organized the ICT Village Festival by awarding DESTIKA Award to appreciate the villages that play an active role in managing the website. One of the winners of DESTIKA Award is Pejeng Village in Gianyar Bali. The approach used in this study is a qualitative approach that uses the unit of analysis informant with data collecting technique through observation and interview to the Pejeng community in Gianyar Bali, and literature study. The results showed that: first, the form of community participation in the preparatory stage presence and the contribution in the form of the ideas. Second, the preliminary stage on energy, fund, and materials. Third, the maintenance phase of community participation in the form of capability and strength. Community participation in the village website development is expected to promote economic potential with increasing community productivity while maintaining local wisdom.